2016
DOI: 10.1371/journal.pcbi.1005148
|View full text |Cite|
|
Sign up to set email alerts
|

Error-Robust Modes of the Retinal Population Code

Abstract: Across the nervous system, certain population spiking patterns are observed far more frequently than others. A hypothesis about this structure is that these collective activity patterns function as population codewords–collective modes–carrying information distinct from that of any single cell. We investigate this phenomenon in recordings of ∼150 retinal ganglion cells, the retina’s output. We develop a novel statistical model that decomposes the population response into modes; it predicts the distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(67 citation statements)
references
References 94 publications
1
66
0
Order By: Relevance
“…Previous work has demonstrated that clusters of retinal ganglion cell activity exhibit error-correctionnamely, highly reliable activation by the same visual stimulus [12]. Thus, we wanted to test whether the activity of readout neurons in the WTA circuit could similar-ity exhibit error correction.…”
Section: Readout Neurons Exhibit Error Correctionmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous work has demonstrated that clusters of retinal ganglion cell activity exhibit error-correctionnamely, highly reliable activation by the same visual stimulus [12]. Thus, we wanted to test whether the activity of readout neurons in the WTA circuit could similar-ity exhibit error correction.…”
Section: Readout Neurons Exhibit Error Correctionmentioning
confidence: 98%
“…In prior work, we described the probability distribution over neural activity patterns with complex models, such as a hidden Markov model, and used machine learning methods to fit the parameters of these models [12]. While this analysis provided insight into the nature of the population code, downstream neural circuits are almost FIG.…”
Section: A Downstream Circuit Model Whose Readouts Develop Strong Clumentioning
confidence: 99%
See 3 more Smart Citations